Considerable characteristic of second plan of the history of Aristotelian society - V. S. Efremova (Омский научный вестник: Серия "Общество. История. Современность", 2022)
The article presents a study of the first stage of the formation of the Aristotelian Society. Unlike works devoted to the development and study of the meaning of the Society in the general historical and philosophical context, in this article the focus is on the group of scholars and amateurs left without close attention, which formed its ‘network’ basis. The qualitative growth of the membership of the Society, the leveling of the most negative aspects of the manifestation of the Matthew effect, strong local traditions — all these factors played an important role in the history of the development of the Society.